Novel EGFR-mutant mouse models of lung adenocarcinoma reveal adaptive immunity requirement for durable osimertinib response. (1st March 2023) - Kleczko, Emily K.; Le, Anh T.; Hinz, Trista K.; Nguyen, Teresa T.; Navarro, Andre; Hu, Cheng-Jun; Selman, Ana M.; Clambey, Eric T.; Merrick, Daniel T.; Lu, Sizhao; Weiser-Evans, Mary; Nemenoff, Raphael A.; et al.
Abstract: Lung cancers bearing oncogenically-mutated EGFR represent a significant fraction of lung adenocarcinomas (LUADs) for which EGFR-targeting tyrosine kinase inhibitors (TKIs) provide a highly effective therapeutic approach. However, these lung cancers eventually acquire resistance and undergo progression within a characteristically broad treatment duration range. Our previous study of EGFR mutant lung cancer patient biopsies highlighted the positive association of a TKI-induced interferon γ transcriptional response with increased time to treatment progression. To test the hypothesis that host immunity contributes to the TKI response, we developed novel genetically-engineered mouse models of EGFR mutant lung cancer bearing exon 19 deletions (del19) or the L860R missense mutation. Both oncogenic EGFR mouse models developed multifocal LUADs from which transplantable cancer cell lines sensitive to the EGFR-specific TKIs, gefitinib and osimertinib, were derived. When propagated orthotopically in the left lungs of syngeneic C57BL/6 mice, deep and durable shrinkage of the cell line-derived tumors was observed in response to daily treatment with osimertinib. By contrast, orthotopic tumors propagated in immune deficient nu/nu or Rag1 −/− mice exhibited modest tumor shrinkage followed by rapid progression on continuous osimertinib treatment. Importantly, osimertinib treatment significantly increased intratumoral T cell content and decreased neutrophil content relative to diluent treatment. The findings provide strong evidence supporting the requirement for adaptive immunity in the durable therapeutic control of EGFR mutant lung cancer. Highlights: Novel murine models of EGFR mutation-driven lung cancer from which transplantable tumor cell lines were established is reported. Orthotopically-propagated lung tumors in syngeneic hosts exhibit strong and durable response to the 3rd generation TKI, osimertinib. Orthotopic lung tumors propagated in immune-deficient hosts reveal a requirement for adaptive immunity for durable TKI response.